Measuring industry agglomeration and identifying the driving forces - Emma Howard; Carol Newman; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Understanding industry agglomeration and its driving forces is critical for the formulation of industrial policy in developing countries. Crucial to this process is the definition and measurement of agglomeration. We propose a new measure and examine what it reveals about the importance of transport costs, labour market pooling, and technology transfer for agglomeration processes. We contrast this analysis with insights from existing measures in the literature and find very different underlying stories at work. An exceptionally rich set of data from Vietnam makes us confident that our measure is superior at least in developing country contexts.
Keywords: L14; L60; O14; O33; 330; industry agglomeration; technology spillovers; labour market pooling; Vietnam; Industrie; Regionales Cluster; Technologietransfer; Spillover-Effekt; Entwicklungsländer